User elicited gesture-based locomotion techniques for immersive VEs in a seated position: a comparative evaluation - Ganapathi, Priya; Sorathia, Keyur (Frontiers in Virtual Reality, 2023)
Locomotion is a fundamental task for exploring and interacting in virtual environments (VEs), and numerous locomotion techniques have been developed to improve the perceived realism and efficiency of movement in VEs. Gesture-based locomotion techniques have emerged as a more natural and intuitive mode of interaction than controller-based methods of travel in VEs. In this paper, we investigate the intuitiveness, comfort, ease of use, performance, presence, simulation sickness, and user preference of three user-elicited body-based gestures: the Calling gesture, Deictic Pointing gesture, and Mirror Leaning gesture. These gestures are intended to be used in three different seated multitasking scenarios involving virtual travel and various levels of hand engagement in selection. In the first study, participants compared the Calling gesture with the Tapping and Teleportation gestures for Scenario 1, which involved virtual travel only. The Calling gesture was found to be the most intuitive, with increased presence, while the Teleportation gesture was the preferred travel technique. The second study involved participants comparing the Deictic Pointing gesture with the Tapping and Teleportation gestures for Scenario 2, which involved virtual travel and one hand engaged in selection. The Deictic Pointing gesture was found to be more intuitive than the other gestures in terms of performance, comfort, ease of use, and presence. The third study introduced a new group of participants who compared the Mirror Leaning gesture with the Tapping and Teleportation gestures for Scenario 3, which involved virtual travel and both hands engaged in selection. The Mirror Leaning gesture was found to be the most intuitive, with increased presence and performance compared to the other gestures. We compared the gestures of the scenarios in three complementary search tasks: traveling in a straight-line path, moving in a directed path, and moving in an undirected path. We believe that the qualitative and quantitative measures obtained from our studies will help researchers and interaction design experts to design efficient and effective gesture-based locomotion techniques for traveling in a seated position in multitasking VEs.